Stable Carbon Isotope Fractionation of Diethyl Phthalate During Oxic and Anoxic Degradation in Estuarine Sediment - Peng, Xuewei (Asian Journal of Chemistry, 2014)
Diethyl phthalate was degraded by mixed microbial in estuarine sediment under oxic and anoxic conditions in a laboratory-microcosm. The respective degradation rate constants of diethyl phthalate under both conditions were 0.103 and 0.069 day-1, with respective half-lives of 6.7 and 10 days. Stable carbon isotopic fractionation produced by biodegradation of diethyl phthalate was evaluated with compound-specific isotope analysis under both conditions. A small 13C-enrichment in residual diethyl phthalate at advanced stages of biodegradation under both conditions was observed, which was 1.8 and 0.7 %, respectively. The isotopic enrichment observed in the residue provided the direct evidence of diethyl phthalate biodegradation in estuarine sediment.